Media Motion Graphics Untuk Penyampaian Materi â€œBagaimana Manusia Memproses Emosi dan Tahapan Perkembangan (Piaget)â€ - Cendana, Wiputra; Tjhin, Nico Tanles (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
Abstract The goal to be achieved in writing Interactive Media and Learning paper is to make interactive learning design of human emotions and stages of human cognitive development based on a theory by Jean Piaget. This was motivated by the repetition of the same material by lecturers to more than 40 students. The university is the highest peak in the formal education level applied in Indonesia, which is taken for 3.5 - 4 years. Students' diverse backgrounds and cognitive skills make them have to keep trying to absorb the content from the lectures. Multimedia Interactive is a media that consists of many components or media that are connected to each other and are able to interact. Teaching media in the form of interactive multimedia has the ability to store audio-visual data, making interactive multimedia especially interactive learning as a supporter of conventional learning methods that were delivered through books and direct explanations without examples are considered to be less easily digested by students, so it is hoped that the use of interactive power point media aims to increase the absorption of material by students who are able to provide information more interesting and enjoyable than just listening to the one-time delivery of material by supporting lecturers. Â Keywords: Emotion, Cognitive Development Stage, Higher Education, Interactive Learning